The Role of Hypothermia in Large Hemispheric Infarction: A Systematic Review and Meta-Analysis - Li, Jing; Gu, Yanghui; Li, Gang; Wang, Lixin; Cheng, Xiaobin; Wang, Min; Zhao, Min (Frontiers in Neurology, 2020)
Abstract Background: Hypothermia is used in the treatment of large hemispheric infarction (LHI); however, its role in outcomes for LHI patients remains ambiguous. This systematic review and meta-analysis was conducted to evaluate the effect of hypothermia on the outcomes of LHI patients. Methods: We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, China Biological Medicine Database, and clinical trials registers before September 21, 2018, and then scanned the reference lists. Randomized controlled trials that compared hypothermia with normothermia in LHI patients were included. Primary outcomes that we reviewed were mortality and neurological outcome. Adverse events during treatment were defined as secondary outcomes. We performed a meta-analysis to calculate pooled risk ratios (RRs), standardized mean differences (SMDs), and 95% confidence intervals (CIs) using fixed-effect models. Results: Three randomized controlled trials involving 131 participants were included. No statistically significant association was revealed between hypothermia and mortality (RR, 1.12; 95% CI, 0.76 to 1.65). There was significant association between hypothermia and good neurological outcome as assessed by modified Rankin Scale score (mRS of 0 to 3) of survivors (RR, 2.09; 95% CI, 1.14 to 3.82), and with neurological outcome by mRS (SMD, -0.54; 95% CI, -1.07 to -0.01). However, significant associations were found between hypothermia and gastrointestinal bleeding, gastric retention, electrolyte derangement, and shivering. No significant differences were detected in the incidence of developing herniation in the rewarming process, pneumonia, cardiac arrhythmia, hemorrhagic transformation, hyperglycemia, hypotension, acute kidney injury, and venous thrombotic events in LHI patients who underwent hypothermia compared with those who had normothermia. Conclusions: This meta-analysis suggested that hypothermia was not associated with mortality in LHI patients. However, it was associated with the improvement of neurological outcome, but with a higher risk of adverse events during treatment. Future studies are needed to demonstrate the efficacy and safety of hypothermia for LHI. The protocol for this systematic review was obtained from PROSPERO (registration number: CRD42018111761).